Revitalisasi dan Identifikasi Nilai-Nilai Multikultural Pada Tradisi Lebaran Etnik Betawi di Kelurahan Cakung Barat, Kecamatan Cakung DKI Jakarta - Abdul Fadhil; Andy Hadiyanto; Ahmad ` Hakam; Amaliyah Amaliyah; Dewi Anggraeni (Balai Penelitian dan Pengembangan Agama Jakarta, 2019)
This research aims to describe multicultural values ​​in the Lebaran tradition of the Betawi community and the process of revitalizing multicultural values. The this time the attitude of empathy, tolerance, social solidarity, equality and justice began to reduce along with the fulfillment of biological needs and egocentric attitudes. Betawi people have a local tradition to be used as a standard for life, religion and community. The local traditions that continues to this day is the lebaran tradition or